Transient opening of trimeric prefusion RSV F proteins - Gilman, Morgan S. A. (Nat Commun, 2019)
The respiratory syncytial virus (RSV) F glycoprotein is a class I fusion protein that mediates viral entry and is a major target of neutralizing antibodies. Structures of prefusion forms of RSV F, as well as other class I fusion proteins, have revealed compact trimeric arrangements, yet whether these trimeric forms can transiently open remains unknown. Here, we perform structural and biochemical studies on a recently isolated antibody, CR9501, and demonstrate that it enhances the opening of prefusion-stabilized RSV F trimers. The 3.3 Å crystal structure of monomeric RSV F bound to CR9501, combined with analysis of over 25 previously determined RSV F structures, reveals a breathing motion of the prefusion conformation. We also demonstrate that full-length RSV F trimers transiently open and dissociate on the cell surface. Collectively, these findings have implications for the function of class I fusion proteins, as well as antibody prophylaxis and vaccine development for RSV.